Phacoemulsification under Topical Anesthesia Alone Versus Topical Anesthesia with Subconjunctival - Javed, Ejaz Ahmad (Pakistan Journal of Ophthalmology, 2010)
Purpose: To compare and determine patients and surgeon’s comfort and satisfaction in Phacoemulsification under topical anesthesia with proparacain hydrochloride 0.5% versus subconjunctival infiltration of 2% lignocaine. Material and Methods: The study was conducted in the department of Ophthalmology Allied and DHQ Hospitals, PMC Faisalabad from May 2008 to June 2009. 90 patients of cataract divided into two groups, A and B each containing 45 patients were included in this study. Phacoemulsification was performed on group A under topical anesthesia with proparacaine hydrochloride 0.5% and on group B under topical anesthesia alongwith subconjunctival infiltration of 2% lignocaine. All the patients in both groups were operated by same surgeon. The surgeon and patients satisfaction score was entered in a standardized Performa. Results: 40 patients (88.89 %) in group A, felt no pain while 5 patients(11.11%) felt pain up to the extent that 0.5 cc of 2 % lignocaine was needed to infiltrate at the phaco port site in the conjunctiva and then the procedure of phacoemulsification was completed comfortably and pain free. In one patient (2.22%) in group A, the nucleus dropped into the vitreous and was referred to vitroretinal surgeon for further management. The mean phaco time was 2.1 minutes while mean operation time was 25 minutes. In group B, the patients were operated after infiltration of 0.5 cc 2 % lignocaine injection in the conjunctiva at phaco port site. All the patients were operated pain free while 10 patients (22.22%) in this group showed bleeding at the phaco port site. This bleeding was managed with a swab on gentle pressure for two minutes. The mean phaco time was 2.0 minutes and mean operation time was 25.0 minutes. The extension of ccc was seen in 5 patients(11.11% ) in group A and 2 patients(4.44 ) in group B .The posterior capsule rent was seen in 2 patients (4.44% ) in A group and in 2 patients(4.44% ) in group B. Conclusion: The subconjunctival infiltration of 2% lignocaine injection near phaco port site is superior to topical anesthesia with proparacaine hydrochloride during phacoemulsification in ensuring patient’s and surgeon’s comfort. None of the patients in any group showed the complications as sometimes seen in periocular or retrobulbar anesthesia.